Anticipated Affect That Encourages or Discourages Human Papillomavirus Vaccination: A Scoping Review - Tsuyoshi Okuhara; Marina Terada; Yumi Kagawa; Hiroko Okada; Takahiro Kiuchi (Vaccines, 2023)
We reviewed studies that examined the anticipated affects associated with human papillomavirus (HPV) vaccination to identify gaps in the literature and the currently available practice implications for encouraging HPV vaccination. We systematically searched MEDLINE, the Cumulative Index to Nursing and Allied Health Literature, PsycINFO, PsycArticles, Academic Search Complete, Scopus, and Web of Science to find English articles that quantitatively and qualitatively examined anticipated affects associated with HPV vaccination. A total of twenty-one studies were identified. Seventeen studies examined the anticipated inaction regret (i.e., not being vaccinated). Most of the included studies reported that anticipated inaction regret had a significantly positive association with HPV vaccination outcomes, such as vaccination behavior, intention, willingness, and acceptability. Furthermore, seven studies reported that anticipated inaction regret had a significantly positive and stronger association with vaccination outcomes than cognitive beliefs, such as vaccine effectiveness and safety, and perceived susceptibility and severity. The present review indicated that the stronger the participants’ anticipated inaction regret, the more likely they were to receive the HPV vaccine. Messages targeting the anticipated affect may be as effective as or more effective than messages targeting cognitive beliefs in encouraging HPV vaccination among people. However, most of the studies included in the present review adopted a cross-sectional design with vaccination intention and willingness as outcomes. Therefore, future studies should examine the influence of anticipated affects on the utilization of HPV vaccines using experimental designs to accumulate stronger evidence.